Pemanfaatan Aplikasi Smartphone untuk Mengembangkan Produk Industri Rumah Tangga - Lila Maria Kaban; Rifin Khong; Jony, Jony; Sylvia, Sylvia (Yayasan Literasi Sains Indonesia, 2024)
The use of smartphone applications for marketing home industry products has gained significant attention in recent years. Smartphone applications are effective tools for entrepreneurship development, particularly for young entrepreneurs, with significant potential for enhancing market reach and customer engagement. This community service took place in Rumah Rahpia, family-style orphanages that play a crucial role in the upbringing and development of teenagers in Medan, Indonesia. Extension and assistance activities in product marketing were carried out for 4 months starting from March to June 2022. Empowering young people in orphanages with entrepreneurial skills is believed to contribute to their personal development and future success. Moreover, fostering entrepreneurship at a young age can help them build realistic career paths and adapt to global trends. Therefore, educating young people in orphanages not only provides them with essential skills and knowledge but also contributes to their overall well-being and prospects. Interviews with the participants show that product sales increased with better product quality after carrying out this community service activity.